FMCW Radar Based Human Detection System for Smart Home Security: Sistem Deteksi Manusia Berbasis Radar FMCW untuk Keamanan Rumah Pintar - Yuswono Hariswanda; Shazana Dhiya Ayuni (Indonesian Journal of Innovation Studies, 2026)
This study addresses the development of a home security system utilizing Frequency Modulated Continuous Wave radar for human presence detection. General Background: Home security systems require reliable detection technologies capable of operating under various environmental conditions. Specific Background: Conventional systems such as CCTV and PIR sensors face limitations in low-light and obstructed environments. Knowledge Gap: There is a need for a detection system that maintains accuracy regardless of lighting and can detect through obstacles. Aims: This study aims to design and implement a human detection system using a 24 GHz HLK-LD2450 sensor integrated with an ESP32 microcontroller and Telegram-based notification system. Results: The system successfully detects human presence in real time within a 6-meter range and ±60° angle, providing stable measurements of position, distance, and speed, with consistent updates every eight seconds. Novelty: The integration of FMCW radar with real-time Telegram notifications provides a combined local and remote monitoring capability under non-line-of-sight conditions. Implications: The proposed system offers a practical solution for improving home security by enabling reliable detection in diverse environmental conditions and enhancing remote monitoring capabilities. Keywords: Fmcw Radar, Human Detection, Home Security System, Esp32, Telegram Notification Key Findings Highlights Real-time tracking provides stable spatial and motion data in indoor environments Radar sensing enables detection under obstructed and low-light conditions Integrated messaging system delivers continuous remote monitoring capability